(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
• This article is a deep, logical and rational analysis of the three original nuclear and chemical elements of the architecture of the nuclear universe, and which give superconducting motion to the solar system and galaxies of the universe. • After the so-called Big Bang of the universe came the space, a new time count and the nuclear universe, governed by the attractions and repulsions of the physical properties of the nuclear superconductivity mass. • Then, three new superconductive materials emerged in space consisting of three new nuclear chemical elements. • The first liquid superconductive mass of gravity appeared. • Liquid superconductive masses of orbital attraction and the superconductive mass of orbital repulsion were formed. • The mass of gravity by means of a gravitational turmoil and centrifuged the three nuclear masses. • So in this way the solar system was created. • Then, the natural moons were created from the volumetric rest of the matter that formed the planet. • At this early time the moons had the rotational motion on their axis, similar to the planet. • At this early time the planets already had the rotation movement. • In "old age," the moon stopped the rotation and began the revolution movement. • In the 21st century, the Earth’s core is solid or pasty.